2016
DOI: 10.1002/ccd.26399
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of catheter‐based rheolytic and aspiration thrombectomy in children

Abstract: Catheter-based thrombectomy systems are an important adjunctive tool in the treatment of children with thrombotic vessel occlusions. Significant hemodynamic compromise seen when using AngioJet may be minimized by using activation times of ≤5 sec. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…The combined approach resulted in further improvement of flow. This experience corresponds with data reported by Qureshi et al in a cohort of 21 patients who underwent aspiration thrombectomy for thrombosis of venous and arterial vessels . Thrombectomy alone did not usually result in sufficient patency of the affected vessel, particularly systemic veins.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The combined approach resulted in further improvement of flow. This experience corresponds with data reported by Qureshi et al in a cohort of 21 patients who underwent aspiration thrombectomy for thrombosis of venous and arterial vessels . Thrombectomy alone did not usually result in sufficient patency of the affected vessel, particularly systemic veins.…”
Section: Discussionsupporting
confidence: 89%
“…Thrombectomy alone did not usually result in sufficient patency of the affected vessel, particularly systemic veins. Combination of aspiration thrombectomy with angioplasty, stent implantation or rtPA was successful in 16/18 patients who underwent this approach . Following subsequent treatment with low‐molecular‐weight heparin for 3 months, none of our patients developed rethrombosis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Suction embolectomy and thrombus fragmentation with rotation of a pigtail catheter or use of a balloon angioplasty catheter are also treatment modalities that are occasionally used in conjunction with USAT, rheolytic embolectomy, and rotational embolectomy. Perhaps the largest study in the pediatric population, studying 21 aspiration and rheolytic thrombectomies (5 of the pulmonary vasculature) at Texas Children's Hospital, showed that such interventions can be performed safely even in critically ill children with lifethreatening thrombosis (50).…”
Section: New/emerging Conceptsmentioning
confidence: 99%
“…Second, it allowed for prevention of serious electrolyte abnormalities such as hyperkalemia. In particular, procedures that cause hemolysis such as rheolytic thrombectomy using Angiojet, are known to potentially cause acute hyperkalemia even in patients with normal renal function , rendering this procedure particularly risky in the setting of dialysis‐dependent renal failure. Third, clearance of iodinated radiographic contrast was facilitated by the use of intra‐procedural dialysis.…”
Section: Discussionmentioning
confidence: 99%